(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
Consideration of grammar in task-based English as a Specific Purpose (ESP) has grown to be a clique issue in the modern language teaching field. Although Task-Based Language Teaching (TBLT) puts more emphasis on the existence of meaning-based communication, other studies have indicated that form-based teaching is needed to promote a grammatically correct result. By integrating the major theoretical and empirical knowledge, this article offers a viable guide to ESP teachers. It maintains that grammar must be incorporated into meaningful activities using a focus-on-form strategy, and only in that way learners can become both communicatively competent and linguistically accurate.